Are the Sentiments Portrayed in the Chairperson’s Letter to Shareholders Consistent with the Financial Performance? - Abdel-Majid Alsaleem, Albadri; Aldain Abdullah Alshorman, Salah (Jordan Journal of Business Administration, 2024)
This study aims to investigate to what extent the sentiments portrayed in the chairperson’s letter to shareholders are consistent with a firm’s financial performance. The sample of this study comprises 115 chairpersons’ letters to shareholders, representing 13 commercial banks listed in the Amman Stock Exchange (ASE) over a 10-year period (from 2010 through 2019). The chairpersons’ letters to shareholders are analyzed for positive and negative sentiments. Financial performance is measured using return on assets. The data is analyzed using a linear mixed regression model. Communicative disclosure and strategic disclosure are used to explain the relationships found. The findings of this study revealed that the level of financial performance has a significant positive relationship with positive sentiments, while it has a negative and insignificant relationship with negative sentiments. This study concludes that the chairperson’s letter to shareholders is both communicative and strategic.